A methodology for the assessment of domino effect scenarios due to projection of fragments generated by internal explosions of spherical vessels (2016)
The domino effect related to the projection of fragments m an Industrial environment occurs when an element of a system, such as a chemical vessel, undergoes catastrophic fragmentation as the result of an explosion The high-velocity fragments then Impact and damage neighboring systems which then leads to Other dangerous scenarios such as loss of containment, fires or even Other explosions_ Of all industrial accident scenarios, those Involving throwing of fragments have the greatest range from the accident point, well over 1 km. This process has been seen m several major accidents worldwide_ In this work, a methodology for the assessment of that kind of domino effect scenar10 was proposed_ this methodology was developed considering the three steps m which that event is divided: fragment generation, trajectory calculation and Impact damage. In the first step fragmentation patterns were studied using numerical simulations_ For this the Internal explosions of 100 stainless steel 304 vessels with spherical geometry, diameters between 1 m and 20 m and thickness m a range from 10 mm to 90 mm, were simulated With the software of material dynamics modeling ANSYS-AUTODYN.